Spatial and temporal variation of cooking-emitted particles in distinct zones using scanning mobility particle sizer and a network of low-cost sensors - Rubal Dhiman; Rajat Sharma; Akshat Jain; Anirudha Ambekar; Thaseem Thajudeen; Sarath K. Guttikunda (Elsevier, 2024)
Exposure to ambient and household fine-particulate matter is identified as a substantial contributor to premature mortality in India, according to the Global Burden of Disease Studies. This study examines the impacts of typical Indian cooking practices on indoor air quality characteristics by monitoring the evolution of fine and ultrafine particle (UFP) concentration in the dining facility of a residential educational institute in India. The monitoring area was spread across the kitchen (zone 1) and the dining hall (zone 2). A combination of validated low-cost PM sensors (LCS), DustTrak8433, and Scanning Mobility Particle Sizer (SMPS) was utilized for real-time data acquisition while using Liquefied Petroleum Gas (LPG) as the cooking fuel. PM2.5 and UFP concentrations were monitored at 1.3 m and 1.8 m from the floor to assess the vertical variation of pollutants during cooking activities, including breakfast, lunch, and dinner, and processes such as preheating, reheating, stir-frying, and deep-frying. It was found that the prolonged cooking durations involved in high-heat cooking methods like stir-frying and deep-frying resulted in a rise in coarser UFP (300-550 nm) and PM2.5, causing a higher exposure to PM and UFP concentration. PM2.5 levels are higher at upper heights during typical cooking processes because of temperature-driven convection currents and hygroscopic growth of particles due to high humidity levels. Air exchange rates (AER) considerably varied by using chimneys and were low during the controlled (closed doors) compared to mixed ventilation (opened doors) conditions. The maximum AER was obtained during lunch (4.3-9.9 h−1) compared to breakfast (-7.8-6.8 h−1) and dinner (0.55-7.9 h−1). The decrement rate of PM2.5 inside zone 1 was highest during lunch (126 µgm−3 h−1), coinciding with the highest AER during mixed ventilation. It is recommended that improving ventilation and better design of the kitchen can reduce the exposure of PM and UFP in commercial and rural area kitchens.